Unveiling the lead exposure attributed burden in Iran from 1990 to 2019 through the lens of the Global Burden of Disease study 2019 - Hanie Karimi; Sara Mahdavi; Sahar Saeedi Moghaddam; Mohsen Abbasi-Kangevari; Zahra Soleimani; Zahra Esfahani; Masoud Masinaei; Sahar Mohammadi Fateh; Ali Golestani; Arezou Dilmaghani-Marand; Farzad Kompani; Negar Rezaei; et al. (Scientific Reports, 2024)
This study aimed to investigate the estimated burden attributed to lead exposure (LE), at the national and subnational levels from 1990 to 2019 in Iran. The burden attributed to LE was determined through the estimation of deaths, disability-adjusted life years (DALYs), years of life lost (YLLs) and years lived with disability (YLDs) using the comparative risk assessment method of Global Burden of Disease (GBD) study presenting as age-standardized per 100,000 person year (PY) with 95% uncertainty intervals (95% UI). Furthermore, the burden of each disease were recorded independently. Eventually, the age-standardized YLLs, DALYs, deaths and YLDs rates attributed to LE demonstrated a decrease of 50.7%, 48.9%, 38.0%, and 36.4%, respectively, from 1990 to 2019. The most important causes of LE burden are divided into two acute and chronic categories: acute, mainly causes mental disorders (DALYs rate of 36.0 in 2019), and chronic, results in cardiovascular diseases (CVDs) (DALYs rate of 391.8) and chronic kidney diseases (CKDs) (DALYs rate of 26.6), with CVDs bearing the most significant burden. At the sub-national level, a decrease in burden was evident in most provinces; moreover, low and low-middle SDI provinces born the highest burden. The burden increased mainly by ageing and was higher in males than females. It was concluded that although the overall decrease in the burden; still it is high, especially in low and low-middle SDI provinces, in advanced ages and in males. Among IDID, CKDs and CVDs that are the most important causes of LE-attributed burden in Iran; CVDs bear the highest burden.
Keywords: 330; Environmental pollutants; Cardiovascular diseases; Death; Disability-adjusted life years; Global burden of disease; Lead